Root oxygen mitigates methane fluxes in tropical peatlands: data - Girkin, Nicholas T.; Vane, Christopher H.; Turner, Benjamin L.; Ostle, Nicholas J.; Sjagersten, Sofie (Cranfield University, 2021)
Tropical peatlands are a globally important source of methane, a potent greenhouse gas. Vegetation is critical in regulating fluxes, providing a conduit for emissions and regular carbon inputs. However, plant roots also release oxygen, which might mitigate methane efflux through oxidation prior to emission from the peat surface. Here we show, using in situ mesocosms, that root exclusion can reduce methane fluxes by a maximum of 92% depending on species, likely driven by the significant decrease in root inputs of oxygen and changes in the balance of methane transport pathways. Methanotroph abundance decreased with reduced oxygen input, demonstrating a likely mechanism for the observed response. These first methane oxidation estimates for a tropical peatland demonstrate that although plants provide an important pathway for methane loss, this can be balanced by the influence of root oxygen inputs that mitigate peat surface methane emissions. This data includes measurements of methane fluxes, peat organic matter properties as assessed by Rock-Eval pyrolysis, bulk peat properties, and microbial community structure as assessed by phospholipid fatty acid (PLFA) analysis.
Keywords: Tropical peatlands'; 'Tropical peat'; 'Methane'; 'Methanogenesis'; 'Methanotrophy'; 'PLFA'; 'Rock-Eval pyrolysis'; 'Climate Change Processes'; 'Ecology'; 'Environmental Science'; 'Soil Biology'; 'Soil Science'